Desnutrición y anemia ferropénica en niños atendidos en el Centro de salud universitario de Motupe-Loja - Ríos Quezada, Manuel Andrés (2022)
Malnutrition is a pathological state of different degrees of severity and clinical affectation, which affects all countries in the world, especially those that are in the developing world, which becomes much more serious if it is associated with anemia, which in most cases it can be prevented. The general objective of this research was to determine malnutrition and iron deficiency anemia in children treated at the Motupe University Health Center in the city of Loja; identify the degree of malnutrition according to the scale of Federico Gómez; establish the degrees of iron deficiency anemia according to the WHO classification and establish a relationship between these variables, through a qualitative, descriptive, longitudinal approach, with a sample of 62 patients of which 50.00% (n=31) did not they had malnutrition, 46.77% (n=29) presented mild malnutrition, 1.61% (n=1) presented moderate malnutrition and 1.61% (n=1) presented severe malnutrition, likewise 80, 65% (n=50) had mild anemia, 11.29% (n=7) presented moderate anemia and 8.06% (n=5) did not present anemia, the null hypothesis was presented that there is a relationship between the two variables studied and statistical relevance was evidenced by obtaining a value of p = 0.00039134, it was shown that children who had malnutrition also presented some degree of anemia